Supply Chain Analysis of Olive Oil in Germany - Janine Flatau; Volker Hart; Aikaterini Kavallari; Peter Michael Schmitz (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2007)
Olive oil is a typical product of the Mediterranean basin, where almost all of the world production takes place. Due to campaigns for a healthier way of living, consumption of olive oil has also increased in non Mediterranean countries in recent years. As a result of the expanded demand the different participants in the supply chain of olive oil strengthen their efforts to obtain a higher market share in these non-traditional markets. Germany with 82.5 million inhabitants is of special interest for olive oil producing countries as it serves as an attractive export destination. Although during the period 1997/98 Germany imported only about 2.6 % of the world?s imports of olive oil and consumed about 0.9 % of the world consumption, it is considered to be a very dynamic market (Ward et al., 2002). Olive oil becomes more and more popular in Germany not only through the ?for a healthier life? campaigns but also through immigrants coming from the Mediterranean basin. Another reason for the growing popularity of olive oil is the increasing convergence of the consumption habits of the European people as a consequence of the expanded tourism to southern countries. The Germans are integrating the Mediterranean diet into their own habits and thus changing gradually their way of cooking in using more and more olive oil in their dishes. Against this background this report aims to analyse the supply chain of olive oil in Germany. For this purpose the report is organised in five chapters. Following the introduction, the second chapter deals with the demand and the third one with the supply of olive oil in Germany. Quality and labelling issues related with the consumption of olive oil are discussed in the fourth chapter. In the fifth chapter the institutions and organisations in Germany occupied with olive oil are briefly presented. After the conclusions follows the annex including detailed tables.
Keywords: 330